Dreaming of What Might Be: The Knights of Labor in Ontario, 1880-1900 - Kealey, Gregory S.; Palmer, Bryan D. (Cambridge University Press, 1982)
As Canada's most industrialised province, Ontario served as the regional centre of the Noble and Holy Order of the Knights of Labor, an organisation which embodied a late nineteenth-century working-class vision of an alternative to the developing industrial-capitalist society. The Order opposed the exploitation of labor, and cultivated working-class unity by providing an institutional and cultural rallying point for North American workers. By 1886 thousands of industrial workers had enrolled within the ranks of Ontario's local and district assemblies. This book examines the rise and fall of the Order, providing case studies of its experience in Toronto and Hamilton and chronicling its impact across the province. –Publisher's description
Google-Books-ID: y32w_mxffhEC
Keywords: Business & Economics / Labor / General; History / Europe / Renaissance